2016
DOI: 10.18176/jiaci.0053
|View full text |Cite
|
Sign up to set email alerts
|

IgE-Api m 4 Is Useful for Identifying a Particular Phenotype of Bee Venom Allergy

Abstract: Background and Objective: Different clinical behaviors have been identified in patients allergic to bee venom. Compound-resolved diagnosis could be an appropriate tool for investigating these differences. The aims of this study were to analyze whether specific IgE to Api m 4 (sIgE-Api m 4) can identify a particular kind of bee venom allergy and to describe response to bee venom immunotherapy (bVIT). Methods: Prospective study of 31 patients allergic to bee venom who were assigned to phenotype group A (sIgE-Api… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
1
23
0
2
Order By: Relevance
“…260 Interestingly, treatment with one allergen resulted in a reduction of IgE to the second in cases of double sensitization. Api m 4 was found to be a useful marker to identify bee venom allergy, 50,261 and sensitization to Api m 10 poses a risk for failure of bee venom AIT. Consistent with this, Api m 10 was underrepresented in 3 of 5 therapeutic HBV commercial preparations.…”
Section: Hymenoptera and Insectsmentioning
confidence: 99%
“…260 Interestingly, treatment with one allergen resulted in a reduction of IgE to the second in cases of double sensitization. Api m 4 was found to be a useful marker to identify bee venom allergy, 50,261 and sensitization to Api m 10 poses a risk for failure of bee venom AIT. Consistent with this, Api m 10 was underrepresented in 3 of 5 therapeutic HBV commercial preparations.…”
Section: Hymenoptera and Insectsmentioning
confidence: 99%
“…Total or specific IgE levels including specific IgE to recombinant venom marker allergens, however, were not confirmed as independent indicators of severe sting‐induced anaphylaxis . Predominant Api m 4‐specific sensitization was proposed to be an indicator of more severe sting reactions by one group . Skin test negativity despite a convincing history of a systemic sting reaction is considered a common finding in coexisting mastocytosis, but has not been characterized as an independent predictor of severe sting‐induced anaphylaxis.…”
Section: Diagnostic Testsmentioning
confidence: 95%
“…Interestingly, recent studies have shown that Api m 4 sensitization might be a useful marker to identify a particular phenotype of HBV allergy that is associated with a higher risk of systemic reactions during the up-dosing phase of VIT [85,86]. However, it has to be taken into account that in these studies the number of patients was very small and that no other known risk factors for side effects were considered.…”
Section: Accepted Articlementioning
confidence: 99%